Synopsis of lectures from the discipline «Theory and methods of scientific creativity» : full-time students in the specialty 274 «Motor vehicle transport» by educational and qualification level – bachelor - Nazarov, А. (Харківський національний автомобільно-дорожній університет, 2025)
The practical application of methods of scientific creativity of applicants is considered: a systematic approach to solving scientific and creative problems; searching for and selecting the best design solutions; evaluation of the results of scientific and technical creativity, modeling in scientific and technical creativity, organization, types and processes of scientific research and recommendations for presenting the results of scientific research. Intended for bachelors of all forms of study in specialty 274 «Motor vehicle transport».
Keywords: scientific creativity of applicants; methods of theoretical research; evaluation of the results of scientific and technical creativity; modeling in scientific creativity; наукова творчість здобувачів; методи теоретичних досліджень; оцінка результатів науково-технічної творчості; моделювання в науковій творчості; 629.01(07)